PROPOSED STRATEGY TO OPTIMIZE DIGITAL MARKETING ACTIVITY FOR THE BUYER’S JOURNEY OF VEMA ID (The Indonesian Journal of Business Administration, 2021)
The growth in the number of companies operating in Indonesia will always increase every year. To run its business on a daily basis, a company will not be separated from the use of the company's fixed assets. The more of fixed assets of the company used, the greater the work to manage all these fixed assets. Vema ID as a business-to-business (B2B) company that provides barcode-based software named VemaFATS and barcode equipment to help companies manage the company's fixed assets has decreased the number of clients by 82.75% from 29 clients in 2019 to 5 clients in 2020. Apart from knowing the internal and external factors of Vema ID, this research also intends to find out the buying process that is passed by Vema ID and its client’s company which is very time consuming and involves many specific positions within the company. To find out who is involved in the decision-making unit and how the client goes through several stages in the buyer’s journey framework during the buying process, the author uses a qualitative method in the form of interviews with 5 Vema ID clients. From the interview, it is known that each company of the client involves at least 3 people in his company to carry out the buying process. Also, in going through several stages of the buyer's journey, all interviewed clients found VemaFATS through Google and in the interview, it was also known that all of them were looking for other alternatives when taking decision. One of the interview clients reveal that the information about the products provided by Vema ID on the VemaFATS website was somehow lacking. The author proposes several strategies to optimize digital marketing activities that must be carried out along several stages in the buyer's journey. To optimize digital marketing activities in the awareness stage, Vema ID needs to do Search Engine Optimization by Google AdSense and YOAST Subscription. To optimize digital marketing activities from the consideration stage until the decision stage, Vema ID can provide beneficial articles on the website, then create a communication medium on the website and by providing complete information about products and services on the website. Lastly, to optimize digital marketing activities in all stages of the buyer's journey, Vema ID can do social media activation. Keywords: Fixed asset, software, the buyer’s journey, the decision-making unit, Vema ID, VemaFATS